The alleged Triassic palaeodictyopteran is a member of Titanoptera - Shcherbakov, Dmitry E. (Zootaxa, 2011)
A sensational find of Palaeodictyoptera in the Mesozoic was recently reported from the Middle–Late Triassic of Central Asia (Ladinian–Carnian, Madygen Formation). The single, somewhat damaged wing described as Liquia reliquia was compared to nearly all possible groups of Pterygota and concluded to be an aberrant palaeodictyopteran with a concave MA (Béthoux et al. 2010). The venation of Liquia was interpreted correctly, but its taxonomic placement cannot be considered valid. Upon closer examination, the fossil immediately reveals its titanopteran affinities, resulting in the following synonymy: Paratitan Sharov, 1968 = Liquia Bethoux et al., 2010, syn. nov. (Titanoptera Paratitanidae); Paratitan reliquia (Bethoux et al., 2010), comb. nov. So far as known, no palaeodictyopteroids survived into the Mesozoic.